Pengaruh Selfie-Liking dan Penyesuian Diri terhadap Prestasi Belajar Siswa - Sabrida M. Ilyas; Syiva Fitria (Program Studi Bimbingan dan Konseling Islam IAIN Langsa, 2021)
Self-liking behavior that has become a lifestyle for teenagers who are active users of social media in the technology era has the potential to cause a decrease in learning achievement which is part of the mastery of knowledge over skills from student learning outcomes.However, empirical studies that explore self-adjustment in learning for adolescents with selfie-liking behavior have not been widely studied. In this study, the researchers aimed to determine the causal relationship between selfie-liking and self-adjustment in learning with high school student achievement. Data were collected from 223 (male=29.6%, female=70.4%) samples aged 16-17 years from three public high schools in Aceh Tamiang. The instrument used in this study were selfie-liking scale and self-adjustment in learning scale. The achievement was measured by using report score.The results of the regression analysis showed that there was no significant collective effect between selfie-liking and self-adjustment in learning achievement (R² = 0.017; F(2.220) = 1.942; p = .146). Partial regression showed that individually, self-liking was not significant in predicting learning achievement (β = -, 045; p = .529), while self-adjustment in learning was a significant predictor of learning achievement (β = ,142; p = . 005). Based on the above research, guidance and counseling teachers are expected to be able to provide preventive counseling services for the effect of excessive selfie like and provide guidance to subject teachers that although students in online learning still display selfie photos, it is not a negative impact on their mental and achievement.